Arguments and analysis in bioethics - Häyry, Matti. (Value Inquiry Book Series, 2010)
Is there any justification for the common practice of allocating expensive medical resources to rescue a few from rare diseases, when those resources could be used to treat devastating diseases that affect the many? Does the use of Prozac and other anti-depressants make us inauthentic beings? Is it immoral and irrational to have children? What is the force of examples and counterexamples in bioethics? What are the relevance of moral intuition and the role of empirical evidence in bioethical argument? What notion of "function" underlies accounts of the distinction between normality and disease and between therapy and enhancement? Is there an inherent conflict between research aimed at therapy and research aimed at gaining knowledge, such that the very notion of "therapeutic research" is an oxymoron? The twenty-one chapters in this volume strive, through the use of high quality argument and analysis, to get a good deal clearer concerning a range of issues in bioethics, and a range of issues about bioethics. The essays are provocative, indeed, some quite radical and disturbing, as they call into question many common methodological and substantive assumptions in bioethics.